2001
DOI: 10.1002/bit.10015
|View full text |Cite
|
Sign up to set email alerts
|

Protein unfolding during reversed‐phase chromatography: I. Effect of surface properties and duration of adsorption

Abstract: Residue-level features of bovine pancreatic trypsin inhibitor (BPTI) unfolding on reversed-phase chromatography (RPC) surfaces were investigated using hydrogen-deuterium exchange labeling and NMR. A set of silica-based RPC surfaces was used to examine the influence of alkyl chain length and media pore size on adsorbed BPTI conformation. In all cases there was substantial unfolding in the adsorbed state; however, residual protection from exchange was consistently observed. Particle pore size did not influence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…A branched C4-alkyl modified silica RPC surface with 300 Å pores was selected as representative of RPC surfaces commonly used in protein separations. The interaction of BPTI with this surface in the absence of salt was previously documented (McNay and Fernandez, 2001), so the effect of salt could be clearly identified. Furthermore, it was shown that BPTIstructure was not influenced by pore size effects on these C4 surfaces (McNay and Fernandez, 2001).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…A branched C4-alkyl modified silica RPC surface with 300 Å pores was selected as representative of RPC surfaces commonly used in protein separations. The interaction of BPTI with this surface in the absence of salt was previously documented (McNay and Fernandez, 2001), so the effect of salt could be clearly identified. Furthermore, it was shown that BPTIstructure was not influenced by pore size effects on these C4 surfaces (McNay and Fernandez, 2001).…”
Section: Introductionmentioning
confidence: 92%
“…The flow rate for all surface-labeling and control experiments was 2.0 mL/min. After loading, the protein was held on the surface for either 5 min or 2 h. Subsequent aspects of the protocol are as previously described (McNay and Fernandez, 2001) except that the indicated salt concentration was maintained in addition to the buffer system used to control pH in all RPC mobile phases (i.e., label buffer, quench buffer, and elution mixture). Any added salt and elution solvents were removed in the size-exclusion step via buffer exchange into 10 mM sodium acetate (NaAc), pH* 2.8.…”
Section: Hydrogen Exchange Labeled Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such unfolding has resulted in an increased apparent footprint of the protein (Wertz and Santore, 1999), increased solvent accessibility (McNay and Fernandez, 2001), and decreased density of adsorbed protein molecules (Vörös, 2004).…”
Section: Effect Of Protein Loading Adsorption Time and Mobile Phasementioning
confidence: 99%
“…There are also examples in which protein adsorption is a desired feature, as long as this can be done in a controlled manner, so that the structural and functional integrity of the protein is maintained. Examples of such areas are the production of combined, adsorbed vaccines (3) and the development of chromatography material (4,5).…”
mentioning
confidence: 99%